Toxicological assessment of the aqueous leaves extract of Combretum platypterum (Welw) Hutch & Dalziel - UWAYA , DICKSON UWAYA; Idu, MacDonald (Algerian Journal of Biosciences, 2022)
Combretum platypterum belongs to the family of Combretaceae. The leaf is used to treat fever, conjunctivitis, febrifuge, coughs, sexually transmitted diseases, diarrhea, and as a tonic. Despite it being used in ethnomedicine to treat various sicknesses, the safety profile of the leaf extract has not been reported. This study was aimed at testing the acute and sub-acute toxicological assessments of the aqueous leaf extract of Combretum platypterum.The acute study was carried out using mice and rats. In sub-acute experiments, the animals received 0.5, 1, and 2.5 g/kg of the plant extract orally per day for 28 days. The first weight and the last weight were taken. The liver, spleen, kidney, heart, lungs, and stomach were obtained, weighed, and fixed. Blood was obtained for haematology and biochemical assays. The LD50 of the root extract was indeterminable since there was no death in the mice and rats used. The leaf extract significantly increases (p<0.05) the body weight at the dose of 2.5g/kg compared to control. The body weight index was not affected compared to control (p>0.05). At 0.5 and 1 g/kg, the extract significantly increased the level of monocytes (p < 0.05) compared to the control. haematological parameters were not affected. Upon bichemical analysis of the leaf extract, 2.5 g/kg significantly (P<0.05) increased the level of HDL and 0.5 and 1 g/kg significantly (P<0.05) increased the level of TRI compared to control. Other parameters were not affected. This study shows that aqueous root extract is safe.